Permanent characterization of bituminous mix: laboratorial characterization tests - Gardete, Dinis (2005)
In the last years some laboratory testing has been used to predict the permanent deformation behavior of bituminous mixtures. The tests methods used in Portugal include the Wheel Tracking test, the Cyclic Compression Test (Uniaxial and Triaxial) and the Repetitive Shear at Constant Height (RSCH) test. There are also the new European standards for those tests methods, with the exception of the RSCH which is essentially used in the USA. Some of testing conditions are not well defined. Therefore, it is important to study the reliability and accuracy of each test in the task of predicting permanent deformation behaviour. In this work these test methods were used in the evaluation of a commonly used mixture in Portugal. Results show that all tests are suitable for predicting permanent deformation behaviour. Thus simpler and cheaper tests are the more interesting to use.